Factors Affecting E-Commerce Customer Loyalty In Indonesia - Felix Harris Kristanto; Hijria Wimanda Rahma; Muhammad Nahrowi (CV. Syntax Corporation Indonesia, 2022)
Digital growth in Indonesia, especially e-commerce is very fast, competition between online businesses is getting tighter. Customers easily move from one place to another to get the best. In a marketing strategy in a time where competition is so fierce today, the most important thing for marketers is to maintain good relationships with customers, in other statement, the challenge and priority of the e-commerce business is to maintain loyalty. Loyalty, customer satisfaction, and customer trust in the e-commerce context are expected to be the critical factors in determining e-commerce success. The design of e-commerce mobile applications, customer service quality, and promotion offers are closely contributed to these factors. However, despite its growth, previous studies confirmed that sustaining customer loyalty is challenging for e-commerce providers. This study aimed at understanding the factors that contributed to keeping customers continue using e-commerce in the Indonesian market. This quantitative research involved 323 respondents who performed repeat online buying on certain e-commerce mobile applications. The data was collected through an online questionnaire consisting of statements on a Likert scale. SmartPLS was used as the data analysis tool. The study's outcomes confirmed that customer satisfaction and promotion offers have a significant impact on customer loyalty. Customer service quality, promotion offers, and mobile applications design of e-commerce influenced customer satisfaction. customer trust has a minor impact on loyalty, and discount promotions have a minor impact on consumer trust as well. The study's results show that customer loyalty is impacted by service quality, effective application design, and leads to customer happiness; customer satisfaction creates loyalty.